Phenolic compounds, antimicrobial activity, cytotoxicity, and identification of phytochemicals present in Inga marginata Willd seeds - Flores, Déborah Cristina Barcelos; Boeira, Caroline Pagnossim; Rolim, Clarice Madalena Bueno; Librelotto, Daniele Rubert Nogueira; Reis, Frederico Luiz; Morandini, Liziane Maria Barassuol; Morel, Ademir Farias; Rosa, Claudia Severo da (Ciência e Natura, 2021)
Brazil has an invaluable source of plants and fruits rich in phenolic compounds important to health, some of which have yet to be discovered. Inga marginata Willd is a fruit that can be found throughout Brazil, and its seeds are rich in phenolic compounds and antimicrobial activity, thus making their extraction and characterization highly relevant. This study aimed to determine the total phenolic compounds, antioxidant capacity, antibacterial and antifungal activities, cytotoxicity evaluation, and characterize the phytochemical compounds present in the extract. The results indicated that extraction by agitation at 30 ºC obtained the highest yield of total phenolic compounds (48.23 mg GAE g-1), antioxidant capacity (40.34 mg TEAC g-1), and IC50 (2.60 mg mL-1). The extracts at 30 and 60 ºC inhibited all microorganisms tested, and the temperature of 30 ºC acted as a bactericide and fungicide at low concentrations. Ten phytochemical compounds were found, mainly being antioxidants and antimicrobials. The cytotoxicity assays showed that Inga marginata seeds do not present cellular cytotoxicity up to the concentration of 250 µg mL-1, maintaining cell viability above 90%.